Knowledge about Sex Education in Adolescence: A Cross-Sectional Study - Maria Teresa Moreira; Elizabeth Rocha; Andreia Lima; Lúcia Pereira; Sílvia Rodrigues; Carla Sílvia Fernandes (MDPI AG, 2023)
(1) Background: In adolescence, the onset of physical signs of sexual maturity and early sexual contact have become increasingly common. However, most adolescents are not adequately prepared for this event, which can lead to significant negative consequences for young people. This study aimed to evaluate knowledge about sexuality during adolescence. (2) Methods: A quantitative, descriptive, and correlational design was used, with 289 students from a school in the northern region of Portugal. From an online questionnaire, sociodemographic information and the Sexuality Knowledge Questionnaire were used to collect data. (3) Results: Most adolescents (54.0%) were female and aged between 15 and 17 years, with an average knowledge score of 17.04. The worst results were found in the dimensions of first sexual intercourse and sexual concerns, with men scoring lower, and the dimension of sexually transmitted infections and HIV/AIDS, where women performed better. The best scores were in the sexuality and sexual pleasure dimension, with women performing better, and the counseling and care in sexual and reproductive health dimension, where men performed better. (4) Conclusions: The approach to sexuality education must be constant throughout the life cycle, and it is essential to provide appropriate information to adolescents about issues related to sexuality.